The Integration of Generative AI Tools in Academic Writing: Implications for Student Research - Rodafinos, Angelos (Social Education Research, 2025)
This article explores the integration of generative Artificial Intelligence (AI) tools in academia, focusing on their impact on student research and writing at advanced levels. It explores how AI can assist with key tasks such as literature reviews, research question formulation, argument construction, data analysis, and thesis organization. The paper argues that the responsible integration of AI is essential, emphasizing the ongoing need for critical thinking to maintain academic integrity. A qualitative case study illustrates student experiences with AI-assisted academic writing, revealing perceived benefits including increased efficiency and enhanced quality, while emphasizing the necessity of verifying AI outputs and preserving human critical oversight. The discussion further addresses the need for universities to adapt by embedding AI literacy into curricula and establishing clear ethical use policies. The central position asserts that, by embracing AI as a valuable ally rather than prohibiting its use, universities can empower students to enrich their learning experiences and better prepare for success in an AI-driven workforce.